Aberrant mucosal wound repair in the absence of secretory leukocyte protease inhibitor - Angelov, Nikola; Moutsopoulos, Niki; Jeong, Moon-Jin; Nares, Salvador; Ashcroft, Gillian; Wahl, Sharon M. (Thrombosis and Haemostasis, 2004)
Secretory leukocyte protease inhibitor (SLPI) is a cationic serine protease inhibitor with anti-microbial and anti-inflammatory properties found in large quantities in mucosal fluids, including saliva. SLPI is expressed during cutaneous wound healing, however, its role in oral wound repair is unknown. We have used a novel approach involving a murine buccal mucosal acute wound model to investigate the role of SLPI in oral healing. In parallel to the observed cutaneous healing phenotype, an absence of SLPI results in markedly impaired oral wound healing associated with increased inflammation and raised elastase activity. Moreover, matrix deposition was decreased, while MMP activity was enhanced in the oral SLPI null wounds suggesting deregulated proteolysis. Intriguingly, regardless of genotype, reduced collagen deposition was observed in oral compared to dermal wounds, associated with reduced TGF-β expression and decreased fibroblast collagen expression in vitro. We propose that SLPI is a pivotal endogenous factor necessary for optimal tissue repair including intra-oral wound healing. In addition, our model provides a unique opportunity to delineate the cellular and molecular mechanisms underlying the differences between dermal scarring and oral scar-free healing.
Keywords: Wound healing; oral; mucosa; cutaneous; inflammation; SLPI